Grief and personal growth: a comparative study of hadith and medicine - Md Rosli, Najwa Hanim (2016)
Introduction: Grief has been defined as the reaction towards loss with typical symptoms including sadness, anger, guilt, yearning, regret, loneliness, numbness and positive feelings related to individual’s personal experience. Grief has been postulated to occur when a safe and secure bond has been threatened. This loss can be an opportunity for personal growth. It is growth that emerges from difficult life events. It may occur during or after process of grieving. We review three cases related to grief and personal growth. Description of case series: In these three cases, grief and personal growth were observed. Each case occurs in different backgrounds. All three cases presented with episode of grief and subsequently reported personal growth during and after grieving process. In each different situation, which include an adult child and caregiver of patient with dementia, a widow who loss her husband from drowning and a cancer survivor, positive outcome was experienced as personal growth. Discussion: Islam has spoke regarding many stories of personal growth emerging from difficulties. The Prophet (s.a.w.) spoke of a man name Owais Al-Qarnee (r.a.), who took care of his ill mother. He was unknown in this world but had become a known person in Jannah. Moreover, Ummu Salamah (r.a.), whose husband died as a martyr was grieving while she was called for marriage with the Prophet (s.a.w.) and Prophet Ayub (a.s.) who was forebearing and patient with an incurable disease for many years. All these familiar stories from al-hadith have been replicated in recent medical literature. It is important to merge the spiritual aspects of grief and personal growth to understand the concept better and to further apply it in the medical field.